Pombalism and antipombalism in Brazil - Oliveira, Luiz Eduardo (2021)
This article seeks to identify and analyze the way in which the educational reforms promoted during the administration of the minister of the king D. José I were represented in two moments that, although belonging to different contexts, have in common the fact that they motivated the organization of events, celebrations and, above all, publications about the marquis of Pombal: the centenary of his death, celebrated in 1882, and his bicentenary, in 1982. Our goal is to understand how the pombalist and antipombalist currents had repercussions or interfered in the historical readings and interpretations of the Pombaline educational reforms, based on the analysis of some texts (biographical, essayistic and historiographical) published on these two occasions.